Components of computer-oriented methods of formation of professional competence of future philologists - S. M. Protska (Academy of Cognitive and Natural Sciences, 2015)
Research goals: reveal the interdependence of components of computer oriented methods of formation of professional competence of future philologists. Research objectives: outline the essential computer oriented methods of formation of professional competence of future philologists in the modern institution of higher education; discover the interdependence of the components of computer oriented methods of formation of professional competence of future philologists; consider the practical aspects of computer components oriented methods of forming professional competence of future philologists. Object of research: the formation of professional competence of future philologists of computer-based learning environment. Subject of research: use of components of computer oriented methods of forming professional competence of future philologists. Research methods used: theoretical methods, that analysis of philosophical, psikhologo-pedagogical, ducational-metodichnoy and instructional methodical literatures with the purpose of determination of the state theoretical ground of problem, and also generalization of the got information, front-rank and personal pedagogical experience, in the improvement of organization of studies. Results of the research: use the potential of computer components oriented methods of formation of professional competence of future philologists will let them in the performance of professional tasks to realize not only information technology, but also psychological and educational goals that will lead to a new education innovation level, provide personal development of students. The main conclusions and recommendations: further scientific research directed to the development of pedagogical conditions of monitoring results of applying elements of computer-oriented methods of formation of professional competence of future philologists in the educational process of higher education.